Controls on intra-plate seismicity in southwestern Australia - Dentith, M.; Featherstone, Will (Elsevier BV, 2003)
Although the Southwest Seismic Zone (SWSZ), located about 150 km to the east of Perth in southwestern Australia, is one of the most seismically active areas in Australia, there is little understanding as to why the earthquakes are occurring. An analysis of geophysical, geological and geodetic data from the area suggests that the SWSZ coincides with a Precambrian terrane boundary. Seismic data show that the terrane boundary zone dips at a shallow angle in a northeasterly direction. Reactivation of this 'zone of weakness' in the contemporary stress field (east-west maximum horizontal stress) is interpreted to be the first-order control on seismicity in the region. Gravity data show that the terrane boundary is offset by near-orthogonal structures, which are interpreted as faults. At least one of these trends corresponds with a linear zone of epicentres. The temporal and spatial distributions of epicentres associated with the 1968 Meckering earthquake (ML 6.9) suggest that the second-order distribution of seismicity in the SWSZ can be explained by the 'intersection model', whereby stresses are amplified by space problems associated with displacements on crosscutting faults. It is speculated that a zone of high density and high seismic velocity in the lower crust may also be a second-order control on the local seismicity. However, confirmation awaits better delineation of the extent of this zone.